Registro argentino de manifestaciones neurológicas por coronavirus-19 (COVID-19) - Alessandro, Lucas (Neurología Argentina, 2021)
COVID-19 disease has spread around the world since December 2019. Neurological symptoms are part of its clinical spectrum. OBJECTIVE: To know the neurological manifestations in patients infected by COVID-19 in Argentina. METHODS: Multicenter study conducted in adults, from May 2020 to January 2021, with confirmed COVID-19 and neurological symptoms. Demographic variables, existence of systemic or neurological comorbidities, the form of onset of the infection, alteration in complementary studies and the degree of severity of neurological symptoms were recorded. RESULTS: 817 patients from all over the country were included, 52% male, mean age 38 years, most of them without comorbidities or previous neurological pathology. The first symptom of the infection was neurological in 56.2% of the cases, predominantly headache (69%), then anosmia/ageusia (66%). Myalgias (52%), allodynia/hyperalgesia (18%), and asthenia (6%) were also reported. 3.2% showed diffuse CNS involvement such as encephalopathy or seizures. 1.7% had cerebrovascular complications. Sleep disorders were observed in 3.2%. 6 patients were reported with Guillain Barré (GBS), peripheral neuropathy (3.4%), tongue paresthesia (0.6%), hearing loss (0.4%), plexopathy (0.3%). The severity of neurological symptoms was correlated with age and the existence of comorbidities. CONCLUSIONS: Our results, similar to those of other countries, show two types of neurological symptoms associated with COVID-19: some potentially disabling or fatal such as GBS or encephalitis, and others less devastating, but more frequent such as headache or anosmia that demand increasingly long-term care.